Energy-add multistage detector a novel multiuser detection method for synchronous CDMA systems. - Boariu, A. (IEEE Journal on selected areas in communications)
In synchronous code division multiple access (CDMA) systems, both multiple access interference (MAI) and intersymbol interference (ISI) arise. MAI is present due to the CDMA format while ISI is present due to channel multipath. One approach to overcome these problems is to detect the entire package of data for all users at once. This implies working with matrices with dimensions proportional to the product of the data package length and the number of active users. In this paper, we present an alternative approach. This alternative consists of a type of multistage detector that overcomes the MAI and ISI problems; in addition, it has complexity proportional to the number of CDMA users, is computationally efficient, and is suitable for pipeline implementation which allows fast data processing. Simulations are compared to a derived single user bound for the average bit error probability and the results prove the validity of the proposed detection method